Plasma Metabolic Phenotypes of HPV-Associated versus Smoking-Associated Head and Neck Cancer and Patient Survival - Eldridge, Ronald C.; Uppal, Karan; Hayes, D. Neil; Smith, M. Ryan; Hu, Xin; Qin, Zhaohui S.; Beitler, Jonathan J.; Miller, Andrew H.; Wommack, Evanthia C.; Higgins, Kristin A.; Shin, Dong M.; Ulrich, Bryan; et al. (Cancer epidemiology, biomarkers & prevention, 2021)
Metabolic differences between human papillomavirus (HPV)-associated head and neck squamous cell carcinoma (HNSCC) and smoking-associated HNSCC may partially explain differences in prognosis. The former relies on mitochondrial oxidative phosphorylation (OXPHOS) while the latter relies on glycolysis. These differences have not been studied in blood. We extracted metabolites using untargeted liquid chromatography high-resolution mass spectrometry from pretreatment plasma in a cohort of 55 HPV-associated and 82 smoking-associated HNSCC subjects. Metabolic pathway enrichment analysis of differentially expressed metabolites produced pathway-based signatures. Significant pathways ( < 0.05) were reduced via principal component analysis and assessed with overall survival via Cox models. We classified each subject as glycolytic or OXPHOS phenotype and assessed it with survival. Of 2,410 analyzed metabolites, 191 were differentially expressed. Relative to smoking-associated HNSCC, bile acid biosynthesis ( < 0.0001) and octadecatrienoic acid beta-oxidation ( = 0.01), were upregulated in HPV-associated HNSCC, while galactose metabolism ( = 0.001) and vitamin B6 metabolism ( = 0.01) were downregulated; the first two suggest an OXPHOS phenotype while the latter two suggest glycolytic. First principal components of bile acid biosynthesis [HR = 0.52 per SD; 95% confidence interval (CI), 0.38-0.72; < 0.001] and octadecatrienoic acid beta-oxidation (HR = 0.54 per SD; 95% CI, 0.38-0.78; < 0.001) were significantly associated with overall survival independent of HPV and smoking. The glycolytic versus OXPHOS phenotype was also independently associated with survival (HR = 3.17; 95% CI, 1.07-9.35; = 0.04). Plasma metabolites related to glycolysis and mitochondrial OXPHOS may be biomarkers of HNSCC patient prognosis independent of HPV or smoking. Future investigations should determine whether they predict treatment efficacy. Blood metabolomics may be a useful marker to aid HNSCC patient prognosis.